(untitled) (Medical Forum Monthly, 2023)
Objective: The COVID-19 pandemic first appeared in Wuhan, China, and then spread rapidly throughout the world. Many people still lack proper knowledge and information about COVID-19. It was essential to assess the awareness ratio among the local community particularly university students during the lockdown period. Study Design: Cross-sectional descriptive study Place and Duration of Study: This study was conducted at the University of Sindh from December 2020 to February 2021 during a period of smart lockdown all over Pakistan. Materials and Methods: There were a total of 150 randomly selected male and female university students during the research work. There was an equal number of control group (undergraduate + intermediate) also selected for comparison. The data was statistically calculated in percent and frequencies by using SPSS software version 21. The statistical difference was determined by applying a t-test and the P- value of < 0.05 was set as significant. Results: The results showed that the majority (90%) of university students were unaware of the Standard Operating Procedures (SOPs) related to COVID-19 prevention. Only 11-22% of university students had an awareness regarding social distancing and mask-wearing. 47% of female students at the university had an awareness about washing hands frequently with soap. A very low percentage (26-27%) of both male and female university students had awareness about the important use of hand sanitizers routinely. Most of the students (50%) belonging to the faculty of Natural sciences were aware of dealing with COVID patients in hospitals. Conclusion: The university students were less aware of the COVID-19 precautions and preventive measures compared to undergraduate and intermediate-level students during a lockdown period in 2020-2021 in Hyderabad Sindh Pakistan. Compared to the students from other faculties, the Natural science students were a little bit aware of the COVID-19 SOPs. The female students were more frequent in washing their hands compared to males but the males were more proper in spending time washing hands. The males and females were equally aware of the important use of hand sanitizers. There is a necessity for proper training and awareness campaigns at the university level prior to the next wave of the COVID-19 pandemic in the future.